Activation of a Neospora caninum EGFR-Like Kinase Facilitates Intracellular Parasite Proliferation - Jin, Xiaoxia; Li, Guojiang; Zhang, Xichen; Gong, Pengtao; Yu, Yanhui; Li, Jianhua (Frontiers in Microbiology, 2017)
The Apicomplexan parasite N. caninum, an obligate intracellular protozoan, causes serious diseases in a number of mammalian species, especially in cattle. Infection with N. caninum is associated with abortions in both dairy and beef cattle worldwide which have a major economic impact on the cattle industry. However, the mechanism by which N. caninum proliferates within host cells is poorly understood. EGFR is a protein kinase ubiquitously expressed, present on cell surfaces in numerous species, which has been confirmed to be essential in signal transduction involved in cell growth, proliferation, survival and many other intracellular processes. However, the presence of EGFR in N. caninum and its role in N. caninum proliferation remain unclear. In the present study, we identified a putative EGFR-like kinase in N. caninum, which could be activated in tachyzoites by infection or treatment with rNcMIC3 (containing 4 EGF domains) or human EGF. Blockade of EGFR-like in tachyzoites by AG1478 significantly reduced parasite proliferation in host cells. Our data suggested that the activation of tachyzoite EGFR-like might facilitate the intracellular proliferation of N. caninum.